Gesture and the nature of language - Armstrong, David F. (Cambridge University Press, 1995)
This book proposes a radical alternative to dominant views of the evolution of language, and in particular the origins of syntax. The authors argue that manual and vocal communication developed in parallel, and that the basic elements of syntax are intrinsic to gesture. They draw on evidence from areas such as primatology, anthropology, and linguistics, to present a groundbreaking account of the notion that language emerged through visible bodily action. They go on to examine the implications of their findings for linguistic theory and theories of the biological evolution of the capacity for language. Written in a clear and accessible style, Gesture and the Nature of Language will be indispensable reading for all those interested in the origins of language.